2015
DOI: 10.1016/j.jpowsour.2015.01.109
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging of solid oxide cells operating under electrolysis conditions

Abstract: h i g h l i g h t sHighly sensitive technique for remote temperature measurement of an SOC. Very little temperature variation across the diameter of the cell during operation. Observed switch from endo (electrolysis) to exo (joule heating) thermic regimes. Changes in electroethermal activity is directly observed during operation. a b s t r a c tSolid oxide fuel cells remain at the forefront of research into electrochemical energy conversion technology. More recent interest has focused on operating in electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This group also collaborated with Geller et al later to attribute surface emissivity changes near electrochemically active regions of an SOEC to a change in a ceria electrode's oxidation state [18]. Tachikawa et al implemented a combined visible/NIR imaging technique to distinguish between thermal and emissivity changes in situ [21], while Cumming and Elder used this technique in SOEC applications to observe temperature changes that were sensitive to different cathode environments [22].…”
Section: Introductionmentioning
confidence: 99%
“…This group also collaborated with Geller et al later to attribute surface emissivity changes near electrochemically active regions of an SOEC to a change in a ceria electrode's oxidation state [18]. Tachikawa et al implemented a combined visible/NIR imaging technique to distinguish between thermal and emissivity changes in situ [21], while Cumming and Elder used this technique in SOEC applications to observe temperature changes that were sensitive to different cathode environments [22].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the measurement setup, spatial resolutions of 0.1 to 0.3 mm can be achieved [315,318,319]. A recent specific review on IR thermal imaging of electrochemical systems, including batteries and fuel cells, can be found in Ref.…”
Section: Thermal Imaging and Liquid-crystal Thermographymentioning
confidence: 99%
“…Reproduced from [64] with permission from Elsevier. SOFCs were examined in electrolysis mode by Cumming et al [66,67] who showed that temperature rises were similar irrespective of the location, or absolute temperature of the cell. It was suggested that this observation (which contradicts that reported by Brett et al [64] for operation in fuel cell mode) was as a result of the decreased electrolyte thickness.…”
Section: Dynamic Thermal Imagingmentioning
confidence: 99%